Wedding essentials for same-sex couples. (Toronto : Wedding Concepts, 2005)
Fonds Suzan Daniel (FSD)
Periodiciteit: driemaandelijks
Redactie : 104-50 Nashdene Road, Toronto ON M1V 5J2
Engels
Periodiek